Erro no contexto do direito penal tributário - Vincensi, Lucas Motta (2017)
The topic of error in criminal law has been addressed for many years by law scholars, and has been the subject of numerous researches and scholarly works. On the other hand, an area of law that has gained much prominence in recent years, and which has been exhaustively studied, is the one related to tax crimes. In this way, the present dissertation aims to unite the two themes, conducting a research on the study of criminal-legal error in the context of tax criminal law. The work will deal with the species of error according to the traditional dogmatic (causalist theory), from the study of the dichotomy error of fact-error of law (error facti-error ius), going through the transition to dogmatics proposed by the finalists, especially Hans Welzel, where will be studied the dichotomy error in type-error in prohibition. Subsequently, a more detailed investigation will be made on the error in type and the error in prohibition in the scope of tax criminal law, where a jurisprudential research will also be carried out on the subject. Thus, the dissertation seeks to approach the institute of error under the prism of tax criminal law, investigating its peculiarities and unfoldings.